Implementation and Evaluation of a Preprinted Perioperative Antimicrobial Prophylaxis Order Form in a Teaching Hospital - Paul Au; Suzette Salama; Coleman Rotstein (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the effect of a preprinted perioperative antimicrobial prophylaxis order form on the appropriateness, standardization and cost of surgical prophylaxis.